2021
DOI: 10.1183/13993003.03024-2020
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterisation of extracellular vesicles in exhaled breath condensate and sputum of COPD and severe asthma patients

Abstract: nano-sized (20-1000 nm) membranous structures released from cells, play critical roles in both physiological and pathological processes [1]. Extracellular vesicles can be classified based on their size into small (sEVs; <200 nm, also known as exosomes) and medium (mEVs; >200 nm, also known as microvesicles) [1]. Extracellular vesicles might be a target for personalised medicine, given their content and biological origin [2]. Indeed, extracellular vesicles detected in various biological fluids, including sputum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Notably, the expression of fibulin-3 is correlated with lung function and emphysema Soni et al, 2021 [ 56 ] Intra-alveolar neutrophil-derived microvesicles are associated with disease severity in COPD Evaluate the profiles of intra-alveolar (within BALF) and circulating (within plasma) MVs in COPD patients, characterizing a variety of MV subtype populations Ex vivo Human This study identified a variety of MV subtype populations within the BALF and plasma of COPD patients with a spectrum of disease severity. In this heterogeneous patient cohort ranging from mild to very severe COPD, BALF PMN (i.e., neutrophil) MVs strongly correlate with the BODE index as well as multiple other markers of COPD severity: worsening dyspnea score, degree of airway obstruction and hyperinflation, lung parenchymal damage, and exercise tolerance Lucchetti et al, 2021 [ 57 ] Detection and characterisation of extracellular vesicles in exhaled breath condensate and sputum of COPD and severe asthma patients Investigate whether extracellular vesicles are present and detectable in exhaled breathe condensate (EBC) and to perform a preliminary comparison of their concentrations in COPD and healthy control subjects Ex vivo Human Extracellular vesicles are detectable in EBC and sputum and measurement of EBC mEV concentrations might be more informative in COPD patients Bazzan et al, 2021 [ 58 ] Microvesicles in bronchoalveolar lavage as a potential biomarker of COPD investigate the presence and source of MVs in bronchoalveolar lavage (BAL) of smokers with and without COPD compared with nonsmoking controls Ex vivo Human MVs obtained directly from the lung BAL show that, in response to smoking and to the development of COPD, measurable inflammatory signals in alveolar macrophages can be quantified and that their numbers are related to the pack-years and the decrease in lung function Carpi et al, 2020 [ 59 ] Expression analysis of muscle-specific miRNAs in plasma-derived extracellular vesicles from patients with chronic obstructive pulmonary disease Analyse the expression profiles of EV-derived myo-miRNAs (specifically miR-206, miR-133a-5p, and miR-133a-3p) in plasma samples collected from patients with COPD Ex vivo Human Myo-miRNA are present in EV in the plasma of COPD patients and their expression (miR-206, miR-133a-5p, and miR-133a-3p) can discriminate between COPD patients Shen et al, 2021 [ 60 ] A novel diagnostic signature based on three circulating exosoma...…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Notably, the expression of fibulin-3 is correlated with lung function and emphysema Soni et al, 2021 [ 56 ] Intra-alveolar neutrophil-derived microvesicles are associated with disease severity in COPD Evaluate the profiles of intra-alveolar (within BALF) and circulating (within plasma) MVs in COPD patients, characterizing a variety of MV subtype populations Ex vivo Human This study identified a variety of MV subtype populations within the BALF and plasma of COPD patients with a spectrum of disease severity. In this heterogeneous patient cohort ranging from mild to very severe COPD, BALF PMN (i.e., neutrophil) MVs strongly correlate with the BODE index as well as multiple other markers of COPD severity: worsening dyspnea score, degree of airway obstruction and hyperinflation, lung parenchymal damage, and exercise tolerance Lucchetti et al, 2021 [ 57 ] Detection and characterisation of extracellular vesicles in exhaled breath condensate and sputum of COPD and severe asthma patients Investigate whether extracellular vesicles are present and detectable in exhaled breathe condensate (EBC) and to perform a preliminary comparison of their concentrations in COPD and healthy control subjects Ex vivo Human Extracellular vesicles are detectable in EBC and sputum and measurement of EBC mEV concentrations might be more informative in COPD patients Bazzan et al, 2021 [ 58 ] Microvesicles in bronchoalveolar lavage as a potential biomarker of COPD investigate the presence and source of MVs in bronchoalveolar lavage (BAL) of smokers with and without COPD compared with nonsmoking controls Ex vivo Human MVs obtained directly from the lung BAL show that, in response to smoking and to the development of COPD, measurable inflammatory signals in alveolar macrophages can be quantified and that their numbers are related to the pack-years and the decrease in lung function Carpi et al, 2020 [ 59 ] Expression analysis of muscle-specific miRNAs in plasma-derived extracellular vesicles from patients with chronic obstructive pulmonary disease Analyse the expression profiles of EV-derived myo-miRNAs (specifically miR-206, miR-133a-5p, and miR-133a-3p) in plasma samples collected from patients with COPD Ex vivo Human Myo-miRNA are present in EV in the plasma of COPD patients and their expression (miR-206, miR-133a-5p, and miR-133a-3p) can discriminate between COPD patients Shen et al, 2021 [ 60 ] A novel diagnostic signature based on three circulating exosoma...…”
Section: Resultsmentioning
confidence: 97%
“…Bazzan et al [ 58 ] observed increased levels of EVs from alveolar macrophages in BAL of smokers with COPD compared to smokers without COPD and nonsmokers, which correlated with the pack-years and disease severity according to FEV1. Luccheti et al [ 57 ] observed that EVs are detectable in exhaled breathe condensate (EBC) and sputum of COPD patients but did not identify the cell source of these EVs.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike reports with devices prone to salivary contamination employing comparable analytical methodologies, metabolite and protein content in FA EBC was restricted to at least vesicular material. Whether the membrane compounds detected are of human or microbial origin is still unclear, but past reports of exosomes in EBC (69, 70) and our observation of lung surfactant components point towards the host as their source. Indeed, exosomes often lack housekeeping gene-coding RNA but are rich in rRNA (71) in line with our observations; future metatranscriptomic studies will establish the diversity and origin of FA EBC RNA and whether this includes miRNAs which are established biomarkers for cancer (7275), lung inflammation (7678), and a number of autoimmune disorders (7981).…”
Section: Discussionmentioning
confidence: 87%
“…Unlike reports with devices prone to salivary contamination employing comparable analytical methodologies, metabolite and protein content in FA EBC was restricted to at least vesicular material. Whether the membrane compounds detected are of human or microbial origin is still unclear, but past reports of exosomes in EBC (69,70) and our observation of lung surfactant components point towards the host as their source.…”
Section: Microbiome and Metabolome Analysis In Ebcmentioning
confidence: 92%
“…The diameter of exosomes ranges from 40 to 160 nm ( Li et al, 2022 ), and these structures play an important role in intercellular communication by transferring nucleotides or proteins, which then act accordingly ( Merckx et al, 2020 ). Various exosomes can be detected in various body fluids, including blood, urine ( Makler and Asghar, 2020 ), synovial fluid, breast milk, ascites, thorax-related sputum, bronchoalveolar lavage fluid (BALF), and pleural effusions, which represent a unique tool to study the pathophysiology and biomarker discovery of respiratory diseases ( Kadota et al, 2016 ; Lucchetti et al, 2021 ). Recently, exosomes have been recognized as a novel disease biomarker because they reflect the physiological state and microenvironment of the cell of origin, are readily found in body fluids, and are stable in the extracellular environment ( Kok and Yu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%